Research on the transition marking between the broken line and solid line of expressway. (August 2022) - Yang, Zhen; Qi, Yani; Ji, Xiaojin
Highlights: The transition marking is set between the dotted line and the solid line, Which is regarded as an information carrier to predict the pass-through right of the road ahead. The white mutation dotted line has better visibility and legibility, which is optimal for transition marking. Vehicle distance and speed are two critical factors that impact the transition marking length. The transition marking reduces the probability of solid-line pressing dramatically during lane-changing. Abstract: Drivers often cross the solid line unintentionally during the lane-changing, when the sight distance is blocked by the vehicle ahead. There are significant potential risks to change lanes in solid line area, which would cause traffic flow disruption and traffic safety hazards. If the drivers with limited sight distance can be reminded in advance that the lane marking ahead is a solid line, many drivers will refrain from changing lanes in the restricted area, therefore, it is important to help the drivers with limited sight distance to obtain the information of lane marking ahead. There is limited research on this specific issue presently, nor any relevant regulations or manuals available in China. This paper puts forward a novel concept of transition marking, and a creative approach by adding the transition marking between the broken line and the solid line. The transition marking is considered an information carrier to predict the pass-through right of the road ahead. We have studied the form and length of the transition marking and evaluated its effectiveness through the driving simulation experiment. The form analysis shows that the white mutation broken line has better visibility and legibility. The transition marking length is shown to be closely related to the vehicle speed and distance. The simulation results indicate that the transition marking length is negatively correlated with vehicle distance and positively correlated with speed. Based on the simulation results and detailed statistical analysis, the reference value of transition marking length is proposed. The effectiveness evaluation demonstrates that the transition marking reduces the probability of solid-line crossing during lane-changing dramatically by 92%.